2016
DOI: 10.1002/mgg3.257
|View full text |Cite
|
Sign up to set email alerts
|

Molecular spectrum and differential diagnosis in patients referred with sporadic or autosomal recessive osteogenesis imperfecta

Abstract: BackgroundOsteogenesis imperfecta (OI) is a heterogeneous bone disorder characterized by recurrent fractures. Although most cases of OI have heterozygous mutations in COL1A1 or COL1A2 and show autosomal dominant inheritance, during the last years there has been an explosion in the number of genes responsible for both recessive and dominant forms of this condition. Herein, we have analyzed a cohort of patients with OI, all offspring of unaffected parents, to determine the spectrum of variants accounting for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 46 publications
3
33
0
3
Order By: Relevance
“…This patient had previously been screened for mutations using a NGS gene panel containing 16 OI genes with negative results 9. In addition, homozygosity mapping by SNP arrays in the proband and her two unaffected siblings showed no known OI genes being contained within patient-specific homozygous regions, strongly suggesting a novel recessive gene.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This patient had previously been screened for mutations using a NGS gene panel containing 16 OI genes with negative results 9. In addition, homozygosity mapping by SNP arrays in the proband and her two unaffected siblings showed no known OI genes being contained within patient-specific homozygous regions, strongly suggesting a novel recessive gene.…”
Section: Resultsmentioning
confidence: 99%
“…For patient 4, targeted NGS gene panel screening, SNP array-based homozygosity mapping and exome sequencing were conducted as previously described in the study by Caparros-Martin et al 9. Regions of homozygosity were established using 1 Mb of contiguous homozygous SNPs as the minimum size cut-off value.…”
Section: Methodsmentioning
confidence: 99%
“…duplication) may be indicated by increased numbers of different genotypes . SNP arrays may also help localize recessive disorders in the offspring of consanguineous parents by facilitating homozygosity mapping , whilst regions of LOH can also indicate uniparental isodisomy, which may be relevant to the diagnosis of imprinting disorders such as PHP1b .…”
Section: Clinical Approach To the Patient With A Metabolic Bone Diseasementioning
confidence: 99%
“…Indeed, Caparros-Martin et al 12 analyzed 42 OI probands, all offspring parents, to determine the spectrum of mutated genes and variants detected for these cases. This work confirmed that COL1A1 mutations are responsible for the OI dominant form.…”
Section: Ngs and Collagenopathiesmentioning
confidence: 99%